2016
DOI: 10.1007/s00170-016-8526-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mechanical properties of anisotropic thin-walled tubes under three-dimensional stress state

Abstract: Tube hydro-bulging test is a specialized method to obtain the mechanical properties of tubes when they are deformed under bi-axial stress states. However, the normal stress cannot be ignored in double-sided tube hydroforming process. In order to investigate the mechanical properties of anisotropic thin-walled tubes under three-dimensional stress state, an analytical model for stress component calculation for fixed-end tube under internal and external pressures was proposed. Furthermore, the equivalent stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a previous study, we have found that the strain-hardening exponent n of 5A02 aluminum alloy tubes obtained from double-sided hydro-bulging tests are all lower than that obtained from uniaxial tensile test of axial arc-shaped sample. 27 Assuming that this is analogous to the 2A12 aluminum alloy tube, the smaller n value under complex stress state will make the prediction result to get closer to the experimental values. Certainly, this article mainly focuses on whether external pressure has an influence on the forming limit of tubes.…”
Section: Resultsmentioning
confidence: 85%
“…In a previous study, we have found that the strain-hardening exponent n of 5A02 aluminum alloy tubes obtained from double-sided hydro-bulging tests are all lower than that obtained from uniaxial tensile test of axial arc-shaped sample. 27 Assuming that this is analogous to the 2A12 aluminum alloy tube, the smaller n value under complex stress state will make the prediction result to get closer to the experimental values. Certainly, this article mainly focuses on whether external pressure has an influence on the forming limit of tubes.…”
Section: Resultsmentioning
confidence: 85%
“…Factors of the environment of space include its being a vacuum, microgravity, extreme cold and high temperatures, etc. Extreme environmental conditions tend to reduce the stability of the space-bound mechanism [24][25][26][27]. In the study of the impact arm, Bougeret [28] designed a prototype flight experiment and established a vertical vacuum laboratory.…”
Section: Introductionmentioning
confidence: 99%